2014
DOI: 10.1017/s0950268814003586
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza surveillance in Central and West Africa, 2010–2014

Abstract: Avian influenza virus (AIV) is an important zoonotic pathogen, resulting in global human morbidity and mortality and substantial economic losses to the poultry industry. Poultry and wild birds have transmitted AIV to humans, most frequently subtypes H5 and H7, but also different strains and subtypes of H6, H9, and H10. Determining which birds are AIV reservoirs can help identify human populations that have a high risk of infection with these viruses due to occupational or recreational exposure to the reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This increase could be attributed to the increase in the number of AIV outbreaks recorded within the region, with Nigeria recording 1205 suspected outbreaks [ 100 ] between 2006 and 2007. Additionally, there has been an increase in surveillance studies [ 49 , 51 , 66 , 67 , 85 , 98 , 101 , 102 , 103 , 104 ] regionally and in different countries, improved laboratory diagnostic capacity and generally enhanced surveillance systems aimed at preventing HPAI outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…This increase could be attributed to the increase in the number of AIV outbreaks recorded within the region, with Nigeria recording 1205 suspected outbreaks [ 100 ] between 2006 and 2007. Additionally, there has been an increase in surveillance studies [ 49 , 51 , 66 , 67 , 85 , 98 , 101 , 102 , 103 , 104 ] regionally and in different countries, improved laboratory diagnostic capacity and generally enhanced surveillance systems aimed at preventing HPAI outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…A serosurveillance study of AIV in Ethiopia showed positive correlation between smaller backyard flock size and the presence of viral antibody (Chaka et al, 2013). Furthermore, in Central Africa (Cameroon, Central African Republic, Congo-Brazzaville, Gabon), evidence of AIV was detected in chickens, ducks, songbirds, and kingfishers (Fuller et al, 2015). In Mali (West Africa), AI seroprevalence was significantly higher in backyard birds than the commercial farms (Molia et al, 2011).…”
Section: Avian Influenzamentioning
confidence: 99%
“…As observed in the neighboring Benin and Côte d’Ivoire, none of the animal swabs collected in Togo through 2012 had been positive for influenza A virus, nor had any animal serum tested positive for influenza A virus antibodies (Couacy-Hymann et al, 2012). Again from 2011 through 2014, no avian samples tested positive for influenza virus genome or antibody in the 3 countries (Fuller et al, 2014). However in swine, influenza virus genome was detected, demonstrating that influenza activity in the region is not completely absent and likely transient when present.…”
Section: Introductionmentioning
confidence: 99%